1988
DOI: 10.1002/job.4030090207
|View full text |Cite
|
Sign up to set email alerts
|

Fear, victimization, and stress among urban public school teachers

Abstract: Data from the National Institute of Education's Safe School Study Report suggested that teachers in American urban public schools are emotionally and physically victimized and that the result is heightened level of stress associated with teaching. This study, which is part of larger, longitudinal project, explores the linkages between reported experiences of victimization by 291 urban public school teachers and task‐specific stressors in the performance of the teaching role. The level of reported stress and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 10 publications
1
29
0
2
Order By: Relevance
“…It is no surprise that some studies have fo und “pupil misbehavior” to be a significant factor in models of occupational stress and burnout among teachers. 2630 School-based violence may also play a role in the decision-making process of teachers when considering whether to leave the education field. A study by Smith & Smith found that the threat of violence in schools was the greatest contributing factor teachers faced when leaving an urban school setting.…”
Section: Discussionmentioning
confidence: 99%
“…It is no surprise that some studies have fo und “pupil misbehavior” to be a significant factor in models of occupational stress and burnout among teachers. 2630 School-based violence may also play a role in the decision-making process of teachers when considering whether to leave the education field. A study by Smith & Smith found that the threat of violence in schools was the greatest contributing factor teachers faced when leaving an urban school setting.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that teachers experiencing the highest burnout rates struggled the most to implement new curricular practices (Ransford, Greenberg, Domitrovich, Small, & Jacobson, 2009) and were the least likely to refer students for schoolbased support services (Pas, Bradshaw, Hershfeldt, & Leaf, 2010). Some evidence also suggests that a subset of teachers with the highest rates of stress and burnout are actually the least likely to leave their jobs, a phenomena characterized as on-the-job-retirement, in which teachers are frequently absent, invest less time preparing engaging and creative lessons, and distance themselves from their students and their work (Dworkin, Haney, & Teschow, 1988;Hughes, 2001).…”
Section: Nature and Consequences Of Teacher Stressmentioning
confidence: 94%
“…Teachers reported wanting more contact with their colleagues both professionally and personally and that enhanced relationships with principals and other school leaders would also help alleviate their stress. Although there is a growing literature suggesting that social support can directly impact occupational stress (Bryk & Schneider, 2002;Dworkin et al, 1988), the cellular structure of elementary schools often leaves teachers isolated and struggling privately to manage stressors with little or no support or direction. Bryk and Schneider (2002) conceptualize these collegial interactions in the context of relational trust, characterized by mutual respect and personal regard that facilitates risk taking and experimentation with new practices.…”
Section: Additional Resources and Supports Neededmentioning
confidence: 99%
“…Additionally, consistent with Lynch's (1987) recommendation that potential victims be studied within limited domain-specific models (e.g., focusing on a particular component of victimization), this study assessed the fear of victimization among rural school personnel and their personal coping measures used to protect themselves and family members against victimization by students and parents/guardians (past and present) in a specific place-outside the school setting. Although there has been extensive research on the fear of victimization among school teachers (Dworkin and Haney 1988;Ricketts 2007;Vettenberg 2002), no study to date has examined the fear of victimization of school staff outside the school setting. As such, this study examines the fear of victimization among school personnel (teachers and staff) off school property, expanding the issue of school violence beyond the workplace.…”
Section: Discussionmentioning
confidence: 98%
“…Previous self-report studies assessing teaching staff perceptions reveal that the physical, organizational and social climate, prior violent experiences, victimization, and the fear of crime, adversely affect job satisfaction levels. These reduced levels of job satisfaction ultimately may lead to higher levels of stress and fear (Dworkin et al 1988;Roberts et al 2007;Vettenburg 2002;Williams et al 1989), often resulting in decreased levels of trust and increased avoidance of certain activities or locations in the school (Marachi et al 2007;Ting et al 2002). Also, the results from studies examining the relationship between fear of victimization and gender have found that women who experienced bullying, harassment, and violence reported lower scores of physical well-being and general health (Gunnarsdottir et al 2006).…”
Section: The Literaturementioning
confidence: 93%